Disordered T cell-B cell interactions in autoantibody-positive inflammatory arthritis - Julé, Amélie M.; Lam, Ki Pui; Taylor, Maria; Hoyt, Kacie J.; Wei, Kevin; Gutierrez-Arcelus, Maria; Case, Siobhan M.; Chandler, Mia; Chang, Margaret H.; Cohen, Ezra M.; Dedeoglu, Fatma; Halyabar, Olha; et al. (Frontiers in Immunology, 2023)
T peripheral helper (Tph) cells, identified in the synovium of adults with seropositive rheumatoid arthritis, drive B cell maturation and antibody production in non-lymphoid tissues. We sought to determine if similarly dysregulated T cell-B cell interactions underlie another form of inflammatory arthritis, juvenile oligoarthritis (oligo JIA). Clonally expanded Tph cells able to promote B cell antibody production preferentially accumulated in the synovial fluid (SF) of oligo JIA patients with antinuclear antibodies (ANA) compared to autoantibody-negative patients. Single-cell transcriptomics enabled further definition of the Tph gene signature in inflamed tissues and showed that Tph cells from ANA-positive patients upregulated genes associated with B cell help to a greater extent than patients without autoantibodies. T cells that co-expressed regulatory T and B cell-help factors were identified, and named T peripheral regulatory (Tpr) cells. The phenotype of Tpr cells suggests an ability to restrain T cell-B cell interactions in tissues. Our findings support the central role of disordered T cell-help to B cells in autoantibody-positive arthritides and the potential regulation of local antibody production by Tpr cells.